PERANCANGAN APLIKASI TES KEPRIBADIAN DISC DENGAN PENDEKATAN BERORIENTASI OBJEK - Wenxi, Wenxi; Antonius, Antonius; Tendean, Sandi (LPPM Universitas Widya Dharma Pontianak, 2024)
Personality testing is an activity conducted by individuals to identify and obtain results about their personality traits. One method used for this purpose is the DISC method (Dominant, Influence, Steadiness, Compliance). Implementing this method in personality testing is expected to be beneficial in business, employment, and organizational. Moreover, companies may consider using this test when recruiting employees. The rapid advancement of technology and the widespread use of Android-based mobile devices, reaching 79.96% in 2022, alongside the previously manual administration of personality tests, are primary factors driving the development of a mobile personality test application using the DISC method. This application is designed as a questionnaire to be filled out by individuals, and upon completion, the results will be immediately displayed to them. To enhance the test results, the application will provide general information about the characteristics, common traits, and example jobs associated with each personality type based on the DISC theory. This information aims to help individuals expand their understanding, knowledge, and application of the DISC method across various domains, including education, employment, organizations, and personal development. Additionally, the application implements the Linear Congruential Generator (LCG) as a randomization algorithm for the questionnaire, ensuring that each individual receives unique questions. Keyword: Personality test, DISC, Java, Android, Linear Congruential Generator